ORGANIZATIONAL PRINCIPLES OF THE FORMATION AND DEVELOPMENT OF REGIONAL INTEGRATED STRUCTURES IN DAIRY BREEDING - SMIHUNOVA, Olena; BOGOMOLOVA, Kateryna; MOISEEVA, Natalia; OREL, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The current state of the domestic dairy industry can be characterized as a crisis, which is associated with a reduction in the number of dairy herds of cattle and a decrease in the volume of milk production, which, in turn, causes a decrease in the competitiveness of milk-producing enterprises and is a real threat to the country’s food security. Along with the saturation of the markets with the necessary milk volumes, there is the problem of ensuring the proper quality of raw dairy materials and their processing products. Solving the problem of improving the quality of dairy products for domestic and foreign consumption will increase domestic dairy producers’ competitiveness in domestic and foreign markets. World experience proves the economic feasibility of highly concentrated dairy farming. The technological equipment of dairy farms with a high concentration of livestock allows, along with increasing the productivity of dairy cows, to ensure the appropriate level of milk quality, which is currently a strategic task for Ukraine’s agro-industrial sector. At the same time, small-scale manufacturers proved to be especially significant during the period of full-scale military operations. In order to ensure their competitive development, we consider it necessary to promote their union according to the industry principle. A practical tool that has proven its effectiveness in the leading countries of the world is cooperation. Thanks to the joint use of the resource base, the members of the cooperatives will have broader opportunities for the formation of stable sales channels and the establishment of strict control over the quality of dairy raw materials and finished products, which will ultimately provide them with advantages over competitors in the market. The specificity of dairy cooperatives is the ability to provide savings to their members due to the effect of scale without encroaching on the independence of their implementation of management functions in the production process. The formation of interest in cooperation among small producers certainly requires substantial state support.